’n Reformatoriese Perspektief op die Langtermyndimensie van die Onderwyser se Leierskapsrol (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
An exposition is provided in this article of the long term dimension of the leadership role of the educator from a reformational perspective. Long-term leadership is discussed in relation to several core functions that the leader needs to perform competently, namely, the creation of a vision; alignment around the vision; infusing core values; development and empowerment of learners.